2015
DOI: 10.1111/epi.13123
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and suicidal behavior in neurotypical young adults with childhood‐onset epilepsy

Abstract: OBJECTIVES We examined the association between lifetime, current history of psychiatric disorders, suicidal thoughts and behaviors with childhood-onset epilepsies in a community-based cohort of young adults. METHODS Cases were neurotypical (normal neurological, cognitive, and imaging exams and no evidence of a brain insult responsible for the epilepsy) young adults with childhood-onset epilepsy followed since the onset of their epilepsy approximately 15 years earlier and recruited as part of a community-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…Of the 16 studies that reported associations between childhood chronic physical illness and anxiety, ten studies used a general (unspecified) measure of anxiety (Alwash, Hussein, & Matloub, ; Baldin, Hesdorffer, Caplan, & Berg, ; Ferro et al., ; Gianinazzi et al., ; Kremer, Schieber, Metzler, Schuster, & Erim, ; Ly et al., ; Michel, Rebholz, von der Weid, Bergstraesser, & Kuehni, ; Muller, Hess, & Hager, ; Servitzoglou, Papadatou, Tsiantis, & Vasilatou‐Kosmidis, ; Zeltzer et al., ), and three studies focused on PTSD (Brown, Madan‐Swain, & Lambert, ; Kamibeppu et al., ; Schwartz & Drotar, ). Two studies reported the associations between childhood chronic illness and PTSD as well as general anxiety (Kazak et al., ; Seitz et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 16 studies that reported associations between childhood chronic physical illness and anxiety, ten studies used a general (unspecified) measure of anxiety (Alwash, Hussein, & Matloub, ; Baldin, Hesdorffer, Caplan, & Berg, ; Ferro et al., ; Gianinazzi et al., ; Kremer, Schieber, Metzler, Schuster, & Erim, ; Ly et al., ; Michel, Rebholz, von der Weid, Bergstraesser, & Kuehni, ; Muller, Hess, & Hager, ; Servitzoglou, Papadatou, Tsiantis, & Vasilatou‐Kosmidis, ; Zeltzer et al., ), and three studies focused on PTSD (Brown, Madan‐Swain, & Lambert, ; Kamibeppu et al., ; Schwartz & Drotar, ). Two studies reported the associations between childhood chronic illness and PTSD as well as general anxiety (Kazak et al., ; Seitz et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 528 participants with childhood‐onset epilepsy and 440 physically healthy controls took part in four studies (Alwash et al., ; Baca et al., ; Baldin et al., ; Kokkonen et al., ). Three studies reported the mean age of participants: 22.36 years for individuals with epilepsy and 22.5 years for healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Baldin compared levels of lifetime and current mood disorders and history of suicidal ideations and attempts in young adult cases prospectively followed since the onset of epilepsy in childhood and compared their responses to those of their sibling controls as well as to a populationbased sample of controls. 46 The self-reported Diagnostic Interview Schedule (DIS) was used for these purposes. No evidence of increased current or lifetime psychiatric difficulties was found in cases compared to either control group.…”
Section: Proxy Vs Self-reportmentioning
confidence: 99%
“…Participants were followed prospectively until study conclusion in January of 2014; details of methods, recruitment and follow-up procedures have been previously described. 2326 Reassessment protocols that included evaluation of social outcomes were conducted at 9- (2002–2006) and 15- (2008–2014) years after recruitment into the study; the 15-year (or young adult) follow-up included assessment of 361 cases (59% of initial cases) with epilepsy, including 291 with uncomplicated and 70 with complicated epilepsy presentations (Figure 1). At the 15-year assessment, siblings within 3 years of age of cases who did not have seizures or a neurological disability served as controls (N=173).…”
Section: Methodsmentioning
confidence: 99%